(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study examines the effectiveness of the look-say method in improving students’ reading comprehension skills. The purpose of this study was to determine students’ reading comprehension skills before and after learning by using the look-say method and to test whether there is a significant effect of the look-say method on students’ reading comprehension ability. The research design is experimental in thform of pre-test and post-test with a quantitative approach. The population in this study was class VII SMP Kartika Wirabuana XX-2 Makassar, which consisted of 2 classes with a total of 68 students. The sample in this study was 20 students, 10 students from class VII A and 10 students from class VII B. The instruments used in this study were tests and questionnaires. The test instruments is to measure the effectiveness of the look-say method while the questionnaire instrument is to measure students’ perceptions of using the look- say method. The results showed that the average score of students’ reading comprehension in the pre-test was 53,75 while in the post-test after applying the look-say method was 78,30. This shows that there is a significant increase before and after the application of the look-say method so that this method is effective in improving students’ reading comprehension. For student responses to the use of this method, it concerns a number of things including making students more active in learning to read English, better understanding the content of the material being taught, and making students more active in learning to reading English, better understanding the content of the material being taught, and make students more interested in learning. The conclusion of this study is that it is effective for use in improving students’ reading comprehension.